DOMESTIC WASTEWATER TREATMENT USING VERMIFILTER COMBINED WITH CANNA INDICA - Joko Sutrisno; Indah Nurhayati; Muhammad Al Kholif; Dinda Rahmaniasari (Universitas Trisakti, 2022)
Untreated domestic wastewater can pollute the aquatic ecosystem. Vermifilter integrated with the Canna indica plant is one of the technological alternatives that can be used to treat domestic wastewater. One of affecting the performance of vermifilters is the vermibed media. Aim: This study aims to examine the effect of vermibed material on the concentration of COD, TP, DO, and the pH value of domestic wastewater treated with vermifilter combined with Canna indica plants. Methodology and Results: The research was conducted on a laboratory scale with a a continuous system using a plastic reactor dimension of 59 x 38 x 29 cm, which is filled with sand filter media, coconut fiber, gravel, and vermibed. The vermibed reactor consists of 4 reactors including reactor 1 (R1) vegetable vermibed, reactor 2 (R2) sawdust, reactor 3 (R3) banana peel, and reactor 4 (R4) cow dung. The results showed that at the end of the research, the best performance is showed by reactor R2 that able to decrease COD 94.81%, TP 92.07%, DO increase 320.00%, pH 6.30±0.10. Vermibed sawdust (R2) can lower COD, TP and raise DO higher to treat domestic wastewater by combining vermifilter with Canna indica plant. Conclusion, significance, and impact study: Vermifilter with Canna indica plant is an effective wastewater treatment in reducing COD, TP, increasing DO and pH value. This treatment is easy processing of operation and maintenance, does not require large land, can be done on an individual scale, and is environmentally friendly.